A tsunami deposit at the Cretaceous/Paleogene boundary in the Neuquén Basin of Argentina - Scasso, Roberto Adrian (2005)
A coarse-grained sandstone bed of Cretaceous/Paleogene (K/Pg) boundary age occurs in a homogeneous neritic shelf mudstone sequence (Jagüel Formation) in the Neuquén Basin of Argentina. This bed, 15 - 25 cm thick, contains abundant plagioclase, broken shells and sharks' teeth. Sedimentological features include an erosive base, abundant rip-up clasts, normal grading and hummocky cross-bedding. The K/Pg boundary age of the bed was confirmed by calcareous nannofossils. Similar to other sections in the Gulf Coast region and the Danish Basin, a "dead zone" significantly depleted in macrofossils is evident in the basal 1 m above the clastic layer. In combination, these features suggest that the clastic layer represents a tsunami deposit that was related to the Chicxulub impact event in Yucatan/Mexico. Mechanisms of tsunami wave amplification in this extremely distal and somewhat protected setting are poorly understood but the funnel-shape of the basin may have promoted the unusually strong sedimentological response. © 2005 Elsevier Ltd. All rights reserved.